Penerapan Sistem Daya Cadangan Untuk Lemari Vaksin Menggunakan PLTS Pada Puskesmas Sindangbarang Bogor - Hasna Satya Dini; Muhamamd Imbarothur Mowaviq; Sugeng Purwanto; Andi Junaidi; Pawenary Pawenary; Sofitri Rahayu (Sekolah Tinggi Teknik - PLN, 2021)
The temperature stability of the vaccine needs to be designed in such a way as to maintain its quality. Where vaccines are generally placed in a special refrigerator with an internal temperature of around +20C - +80C. The condition of the electricity network in the Bogor area, which sometimes goes out for a long time can cause electricity to not be supplied for vaccine refrigerators. For a long period of time, this condition can cause damage to the vaccine so that it cannot be given to toddlers. This activity is the application of technology that is very useful for the people of the Bogor, especially for the Sindangbarang Health Center in Bogor related to the design of power reserves, especially for vaccine refrigerators. This power backup system uses various equipment with appropriate technology such as Automatic Transfer Switch (ATS), solar panels, inverters, batteries, solar charge controllers and other supporting equipment. This PKM program has a focus on managing backup power systems in vaccine cabinets using solar power plants